Dom Innocent Le Masson, Général des Chartreux: Correspondance, volume 4. Edited by Dom Augustin Devaux. Pp. 147. Illustrated. (Analecta Cartusiana, 206.) Salzburg: Institut für Anglistik und Amerikanistik, 2005. isbn 3 900033 26 9. Paper €40 - Gribbin, Anselm J. (The journal of theological studies, 2006)
Dom Innocent Le Masson, Prior of La Grande Chartreuse (1676–1703), is a major figure in the history of the Carthusian Order. He firmly guided the 170 charterhouses then in existence, rebuilt sections of La Grande Chartreuse after a terrible fire in 1676, issued new Statutes for the Order (1681), and was a noteworthy spiritual writer and the prodigious author of works ranging from canon law and ecclesiastical history to biblical studies and moral theology. The extent of Le Masson's correspondence is astonishing. It has been estimated that on average he wrote sixty letters per week. Dom Augustin Devaux's edition of Le Masson's letters (in three volumes as Analecta Cartusiana, 206), is now furnished with a slimmer, companion volume of indexes in French.